2015
DOI: 10.1007/s00276-015-1469-9
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT scan, electron microscopy and optical microscopy study of insertional traumas of cochlear implants

Abstract: In our opinion, the combination of 3D micro-CT scan reconstructions and histological analysis using OM appears to be the best method to analyze this type of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Earlier studies have shown that micro-CT is feasible for in vitro electrode studies (15)(16)(17). Whereas Le Breton et al (15) concluded that micro-CT is not sufficiently accurate for the reliable assessment of insertion trauma, Postnov et al (17) found nearly equal visualization of the cochlear structures and the electrode array as in histological samples. Similar to our study, Postnov et al removed the perilymph to increase the contrast of the BM and better visualization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown that micro-CT is feasible for in vitro electrode studies (15)(16)(17). Whereas Le Breton et al (15) concluded that micro-CT is not sufficiently accurate for the reliable assessment of insertion trauma, Postnov et al (17) found nearly equal visualization of the cochlear structures and the electrode array as in histological samples. Similar to our study, Postnov et al removed the perilymph to increase the contrast of the BM and better visualization.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-computed tomography (micro-CT) is another feasible imaging modality used for the investigation of cochlear trauma in TB studies (15)(16)(17). It can provide highly detailed images of the cochlea, it is significantly less time-consuming, and it requires no manipulation when compared with histology.…”
Section: Introductionmentioning
confidence: 99%
“…The authors claim that a combination of micro-CT and optical microscopy is necessary to determine the spatial relationships of vessels with different diameters. In medical studies, the combining approach has been proven very efficient to detect cochlear trauma caused by cochlear implantation [ 45 ]. The study concludes that a combination of 2D imaging, 3D imaging, and histology is necessary in order to have reliable results regarding the trauma.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…been reported to provide a resolution of around 10 to 30 µm pixel size (Le Breton et al 2015;Malherbe et al 2013;Voie et al 1993) within the context of cochlear imaging.…”
Section: Opfos An Optical Sectioning Technique and μCt That Is A Radmentioning
confidence: 99%